2016
DOI: 10.18632/oncotarget.12539
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding protein, tristetraprolin in a murine model of recurrent pregnancy loss

Abstract: Recurrent pregnancy loss is a major reproductive pathology affecting 1-5% of pregnant women worldwide. A distinct feature of this reproductive pathology is involvement of key inflammatory cytokines and transcription factors such as tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6) and nuclear factor kappa beta (NF-κB). Special classes of RNA-binding proteins regulate the transcripts of many of these important cytokines and regulatory factors via binding to the 3′ untranslated regions (UTRs) and/or poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The administration of LPS to pregnant mice causes placental degeneration due to acute inflammation, which results in fetal loss 21,22 . Here, we found that the embryo absorption rate and abortion rate were increased in LPS‐activated mice, which confirmed the validity of LPS as a potential inducer of inflammatory response and its associated impact on the placental vasculature 23,24 . Inflammation is reported to link with the pathogenesis of the female reproductive system which causes RSA 25 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The administration of LPS to pregnant mice causes placental degeneration due to acute inflammation, which results in fetal loss 21,22 . Here, we found that the embryo absorption rate and abortion rate were increased in LPS‐activated mice, which confirmed the validity of LPS as a potential inducer of inflammatory response and its associated impact on the placental vasculature 23,24 . Inflammation is reported to link with the pathogenesis of the female reproductive system which causes RSA 25 .…”
Section: Discussionsupporting
confidence: 74%
“…21,22 Here, we found that the embryo absorption rate and abortion rate were increased in LPS-activated mice, which confirmed the validity of LPS as a potential inducer of inflammatory response and its associated impact on the placental vasculature. 23,24 Inflammation is reported to link with the pathogenesis of the female reproductive system which causes RSA. 25 In this study, we found that TMUB1 silencing decreased the expression of inflammatory cytokines in LPS-activated trophoblast cells, indicating the facilitating role of TMUB1 in the inflammatory response during the development of abortion.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Moreover, Kasra Khalaj et al. 26 showed that TTP protein was downregulated in an LPS-induced mouse pregnancy loss model, and its targets TNF-α and interleukin-6 (IL-6) were upregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, sections were counterstained with haematoxylin and bluing reagent for 4 min before adding the coverslips. For CD31 and Ki67 staining, differential cell counting analyses, image analysis software was conducted using NIH ImageJ as per previously published protocol from our group 45 . Briefly, 100 cells were manually counted from three areas from three different slides in each experimental group.…”
Section: Methodsmentioning
confidence: 99%